Analysis of wage distribution in Malaysia - Mahdir Bahar; Assis Kamu; Norhayati Jantan; Darmesah Gabda (2020)
Labor force demand in Malaysia has grown significantly over the decades since the independence era. Changes in economic structure have led to changes in labor force utilization. There are hundreds of studies had been done to investigate the determinants of wages, including human capital factor, demographic factor as well as job characteristic. The objective of this paper is to examine the determinant of wages in Malaysia using the Salaries and Wages Survey, 2016 conducted by the Department of Statistics Malaysia. Based on the analysis of mean differences, the average wage is significantly different for all variables, including age, ethnicity, marital status, education level and occupation. Even in the analysis of the distribution for men and women, the difference in average wage is also identified for each occupation category and sector of the industry.